Study of women’s knowledge of the role of androgens and their excess in women - research article - Ćwik-Błotnicka, Dominika; Nitka, Karolina (Journal of Education, Health and Sport, 2023)
Introduction: excess androgens is one of the most common endocrine disorder in women. The ovaries and/or adrenal glands are responsible for the excess of androgens. The most common cause is polycystic ovary syndrome. The aim of the study: was to show the level of knowledge of the women surveyed about the role of androgens and to find out the degree of their awareness of androgen excess in women. Last but not least, it was important to find out which symptoms the respondents think are characteristic of androgen excess in women, whether they know the concept of hirsutism and what androgenetic alopecia looks like. Material and method: wykorzystano ankietę własnego autorstwa. Przebadano 172 kobiety. Dokonano porównania odpowiedzi na pytania pomiędzy podgrupami. Oparto się na aktualnej literaturze medycznej oraz artykułach oryginalnych i badawczych znalezionych w PubMed. Results: slightly more than half of those surveyed know that testosterone is produced by the ovaries and adrenal cortex. Only 35.5% of the women surveyed can name other hormones belonging to the androgens besides testosterone. 60.7% of women know the characteristic symptoms of hyperandrogenism. 51.7% know the term hirsutism and 32% correctly identify the most common cause. Conclusions: given the prevalence of endocrine disorders in women, it is important to expand and disseminate information on the symptoms and causes of androgen excess in women, especially among women without medical education.